Artificial Intelligence and Multiple Sclerosis: Past, Present, and Future - Amin, Moein; Nakamura, Kunio; Ontaneda, Daniel (Seminars in Neurology, 2025)
Artificial intelligence (AI) in multiple sclerosis (MS) is an area of growing importance of growing importance. We review the historical context, current applications, and future prospects of AI and machine learning (ML) in MS. The review highlights AI's potential to address critical challenges in MS management, including early and accurate diagnosis, individualized treatment strategies, prognostication, and efficient patient monitoring. By leveraging large datasets and high-dimensional data, AI promises profound insights and augments clinical decision-making processes. Additionally, the manuscript covers potential limitations and challenges facing AI use in MS clinical practice and research.
Keywords: artificial intelligence; multiple sclerosis; machine learning